(3JjSjQ GdcQje GdQMef aj JaSjQ cdGe GdefGf (B/s - (3GdSYOj, YHO GdQMef Hf fGUQ Hf YHO Gddg,s 1307-1376 (3gLQjG(B.s; (3GdYbjd, YHO Gddg Hf YHO GdYRjR Hf YHO Gddg,s 1335-1432 (3gLQjs; (3GdYKjejf, eMeO Hf UGdM Hf eMeO,s 1347-1421 (3gLQjG(B.s; (3GdUejd, SYO Hf ahGRs ((3GdOeGe, GdSYhOjI (B:s (3OGQ GHf GdLhRj,s, 2010)
(3jJfGhd GdcJGH JaSjQ cd ShQ GdbQBf GdcQje, jJfGhd cd BjI Ydi MOI(B.s
Keywords: (3GdbQBfs -- (3JaGSjQ MOjKIs